2009
DOI: 10.4142/jvs.2009.10.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Protection of chicken against very virulent IBDV provided by in ovo priming with DNA vaccine and boosting with killed vaccine and the adjuvant effects of plasmid-encoded chicken interleukin-2 and interferon-γ

Abstract: The aim of this study was to examine the efficacy of in ovo prime-boost vaccination against infectious bursal disease virus (IBDV) using a DNA vaccine to prime in ovo followed by a killed-vaccine boost post hatching. In addition, the adjuvant effects of plasmid-encoded chicken interleukin-2 and chicken interferon-γ were tested in conjunction with the vaccine. A plasmid DNA vaccine (pcDNA-VP243) encoding the VP2, VP4, and VP3 proteins of the very virulent IBDV (vvIBDV) SH/92 strain was injected into the amnioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Bursa of Fabricius is responsible for the development of humoral immunity. The bursal lesions were characterized by lymphoid depletion and edema in the follicles, fibroplasias in the interfollicular connective tissues and proliferation of the reticular epithelial cells (Park et al, 2009). A possible explanation of these results might be that dietary methionine and threonine may have interfered with apoptotic or necrotic process of bursal lymphocytes during infection of IBDV because the use of IBD vaccine can cause a varying degree of bursal lymphocytolysis (Amakye-Anim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Bursa of Fabricius is responsible for the development of humoral immunity. The bursal lesions were characterized by lymphoid depletion and edema in the follicles, fibroplasias in the interfollicular connective tissues and proliferation of the reticular epithelial cells (Park et al, 2009). A possible explanation of these results might be that dietary methionine and threonine may have interfered with apoptotic or necrotic process of bursal lymphocytes during infection of IBDV because the use of IBD vaccine can cause a varying degree of bursal lymphocytolysis (Amakye-Anim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A potential use of DNA vaccine for priming in ovo or at 1 day old followed by boosting with inactivated vaccine or vectored vaccine has been described (Haygreen et al, 2006;Hsieh et al, 2007) and induced protection from a virulent challenge infection. The use of DNA vaccination via the in ovo route was also described (Oshop et al, 2003;Haygreen et al, 2006;Park et al, 2009). The results showed that the in ovo delivery without a boost vaccination was not sufficient to induce protective immunity.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, priming it with a DNA vaccine will ensure satisfactory results. The in ovo vaccination method in chicks prevents frequent trouble of multiple vaccine administration . Turkey herpesvirus and fowlpox IBDV vector vaccines via the in ovo route have shown an increased safety profile compared with live IBDV vaccine .…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%